COMMON GRAMMATICAL ERRORS IN STUDENTS’ WRITING (A CASE STUDY OF THE FIRST-YEAR STUDENTS OF IST AKPRIND YOGYAKARTA) - suprih Ambawani (JUPE : Jurnal Pendidikan Mandala, 2022)
This study is intended to find out and describe grammatical errors made by the first-year students of the Statistics  Department of IST AKPRIND Yogyakarta. This study uses a descriptive qualitative method. The data are taken from 30 students’ writing on free topics. The grammatical found are classified based on the surface strategy taxonomy proposed by Dulay et. al. (1982): they are omission errors, addition errors, misformation errors, and misordering errors. The results of the data analysis showed that there were 558 errors of 206 sentences taken from 30 writing that consist of 44.09% misformation errors, 27.06%, omission errors, 22.35% addition errors, and 4.92% misordering errors. From these findings, it was concluded that grammatical errors were caused by interlingual and intralingual interference. Therefore, teachers are suggested to give more emphasis on the structure of English which is different from Bahasa  Indonesia, and pay more attention to the structure of the language that is considered difficult.ist